Light-enhanced antibacterial carbon dot nanocomposite synthesized using Sargassum horneri and inorganic precursors - Kyung Woo Kim; Gun-Woo Oh; Seok-Chun Ko; Ji-Yul Kim; Chul Hwan Kim; Yong Min Kwon; Mi-Jin Yim; Moongeun Yoon; Dae-Sung Lee (Fisheries and Aquatic Sciences)
This study aimed to introduce a novel antibacterial carbon dot-ZnO-TiO2 nanocomposite (CDZT) synthesized from the marine alga Sargassum horneri and two inorganic precursors. CDZT exhibited enhanced antibacterial activity under both ultraviolet (UV) light and visible light, and its water-soluble nature suggested its potential in various industrial applications. The antibacterial activity was evaluated using disk diffusion tests under two different light conditions. CDZT showed distinct bacterial inhibition against both gram-negative and gram-positive strains, with larger inhibition zones under 365 nm UV light and 470 nm visible light, respectively. These results highlighted the promise of S. horneri as a valuable resource for the development of advanced antibacterial materials. The findings underscored the possibility of CDZT being a potent antibacterial agent with light-modulated activity. Since this was a proof-of-concept study, further evaluation is needed for the practical use of CDZT in antibacterial applications within the relevant industry.